On the concavity of some functions connected with the two-dimensional normal distribution - Bodin, N.; Zalgaller, V. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Н. А. Бодин, В. А. Залгаллер. Вогнутость некоторых функций, связанных с двумерных нормальным распределением N. Bodin, V. Zalgaller. Kai kurių funkcijų, susijusių su dvimačiu normaliniu pasiskirstymu, įgaubtumas